2016
DOI: 10.3126/jpn.v6i11.15676
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of ulcerative colitis in colonoscopic biopsies

Abstract: Background: Histopathologic evaluation of colonoscopic mucosal biopsy remains one of the earliest modalities of investigation in patients clinically suspected of ulcerative colitis. Pathologists should be aware of classical histomorphological features to avoid misdiagnosis. The aim of the present study was to evaluate histopathologic features as well as to determine possible atypical presentation.Materials and Methods: Forty newly diagnosed cases of ulcerative colitis were included in the study. Colonoscopic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Study by Surawicz and Belic reported that crypt distortion is also one of the characteristics of IBD besides basal lymphoplasmacytosis (Surawicz & Belic, 1984). Various studies showed distorted architectural crypt in UC could occur ranging from 57% to 100% cases (Dhakhwa et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Study by Surawicz and Belic reported that crypt distortion is also one of the characteristics of IBD besides basal lymphoplasmacytosis (Surawicz & Belic, 1984). Various studies showed distorted architectural crypt in UC could occur ranging from 57% to 100% cases (Dhakhwa et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, FAC patterns can be observed in cases of UC that are resolving under medical treatment, and areas of the colon and rectum that were previously inflamed in UC can return to an almost normal histological appearance. Medications associated with FAC include nonsteroidal anti-inflammatory drugs (NSAIDs), mycophenolic acid, and ipilimumab, among others [11,12]. While diarrhea is the most common reason for a workup in many of these patients, FAC can also be incidentally discovered because of bowel preparation with Phospho-soda in asymptomatic patients undergoing screening colonoscopy [6].…”
Section: Clinical Implications Of Focal Active Colitismentioning
confidence: 99%